FAKTOR YANG TERLIBAT DIDALAM OPINI AUDIT GOING CONCERN PADA PERUSAHAAN SEKTOR PROPERTY DI BURSA EFEK INDONESIA - Haryadi, Dedi; Apriyanto, Vito (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2025)
Going concern opinion as an audit opinion explains the auditor's doubts about the company's performance to operate in the future. Providing audit opinion and explaining the company's condition has a major impact on investment decisions so that auditor independence, integrity and objectivity are required according to professional ethics. This study was conducted with the aim of identifying the effect of prior opinion, opinion shopping, cash flow ratio, and company growth on going concern audit opinion acceptance in property sector companies listed on the Indonesia Stock Exchange. The method used is logistic regression analysis supported by using IBM Statictical Product and Service Solution (SPSS) Version 26 software as a calculation tool. The test results concluded that the study found that prior opinion has a positive influence on going concern audit opinion acceptance while opinion shopping, cash flow ratio and company growth are unable to influence going concern audit opinion acceptance. Taking into account these limitations, it is recommended for future research that researchers consider using different independent variables, measuring variables with alternative ratios, and exploring different company sectors. Furthermore, to improve the accuracy of the research results, it is recommended to increase the number of data samples by adding research years.